2016
DOI: 10.3389/fpls.2016.01409
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Orobanche crenata Infection Severity in Faba Bean, Field Pea, and Grass Pea Productivity

Abstract: Broomrape weeds (Orobanche and Phelipanche spp.) are root holoparasites that feed off a wide range of important crops. Among them, Orobanche crenata attacks legumes complicating their inclusion in cropping systems along the Mediterranean area and West Asia. The detrimental effect of broomrape parasitism in crop yield can reach up to 100% depending on infection severity and the broomrape-crop association. This work provides field data of the consequences of O. crenata infection severity in three legume crops, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…For instance, several Orobanche and Phelipanche species parasitize important crops and are of major importance in Europe, where about 70% of farm land is infected with seeds of broomrapes (Gevezova et al 2012). The effects of Orobanche infection on the growth and mineral composition of the host have been studied in parallel observations of host and parasite (Singh et al 1971;Barker et al 1996;Labrousse et al 2010;Ferna´ndez-Aparicio et al 2016). In all cases, reduction in host biomass was mentioned for both vegetative and reproductive organs.…”
Section: Introductionmentioning
confidence: 91%
“…For instance, several Orobanche and Phelipanche species parasitize important crops and are of major importance in Europe, where about 70% of farm land is infected with seeds of broomrapes (Gevezova et al 2012). The effects of Orobanche infection on the growth and mineral composition of the host have been studied in parallel observations of host and parasite (Singh et al 1971;Barker et al 1996;Labrousse et al 2010;Ferna´ndez-Aparicio et al 2016). In all cases, reduction in host biomass was mentioned for both vegetative and reproductive organs.…”
Section: Introductionmentioning
confidence: 91%
“…Due to their achlorophyllous nature, they are constrained to obtain their nutritional resources by feeding off broad-leaf plants using the haustorium, a unique organ in parasitic plants that links the parasite to the root of the hosts. Through the haustorium, the parasite diverts water, and nutrients from the host (Westwood, 2013), leading to severe yield loss, and quality in numerous vegetables crops (Joel et al, 2007; Pérez-de Luquea et al, 2010; Fernández-Aparicio et al, 2016). It was suggested that once the connection between the parasite and the host roots is established, the parasite functions as an active sink, redirecting solutes away from autotrophic sink tissues and subsequently leading to a decrease in the accumulation of host biomass (Péron et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, compounds not containing the butenolide ring (1 and 7) were not active, including that with the open butenolide (8). (2), grandiflorenic acid (3) and derivatives (9,(13)(14)(15) The addition of the butenolide ring to kaurenoic acid (2) in compounds 9 and 15 led to active compounds in all tested species except O. crenata. The highest activity was found on both Phelipanche spp.…”
Section: Gamentioning
confidence: 99%
“…Broomrapes ( Orobanche and Phelipanche species) and witchweeds ( Striga species) are noxious weeds that are difficult to control in Europe, Africa and Asia . These weeds are root parasites that cause significant yield losses in crops by direct withdrawal of nutritive resources through vascular connections . Each parasitic plant produces massive numbers of seeds with long embryo longevity and easy dispersal, which in turn leads to resilient parasitic seedbanks whose eradication is a challenging agricultural problem .…”
Section: Introductionmentioning
confidence: 99%